PELATIHAN DIGITAL MARKETING: MENINGKATKAN PERTUMBUHAN BISNIS MAHASISWA PROGRAM STUDI ILMU POLITIK FISIP UNIVERSITAS HALU OLEO DI ERA TEKNOLOGI - Lestari, Indra; Arief, Iriyani Astuti; Syahadat, Muh. Ishak; Taya, La; Efrianto, La Ode; Tunda, Amin; Rachim, Muhamad Djufri (Anoa : Jurnal Pengabdian Masyarakat Sosial, Politik, Budaya, Hukum, Ekonomi, 2024)
Digital Marketing Training: Increasing Student Business Growth, for Students of Political Study Program FISIP Halu Oleo University in the Era of Technology, aims to improve students' skills in applying digital marketing in their businesses. Mastering techniques in digital marketing such as using social media and other digital tools will be instrumental for students to develop their business. For this reason, the Service Team carries out digital marketing training in the form of an introduction to effective techniques and tricks in digital marketing, the use of social media, SEO (Search Engine Optimization), SEM (Search Engine Marketing), and other digital tools to support business growth. This is done considering that there is still a lack of digital marketing skills among students in the current technological era, even though if it is well understood, digital marketing will help students improve the business they have so that when they finish their studies, students no longer need to think about looking for work. Still, it can open up employment opportunities for people through the businesses they own. This digital marketing training can make students of the political science study program, FISIP UHO better understand how to utilize technological developments in marketing activities. Current developments in technology and information can be used by students to develop their businesses, by utilizing various existing digital platforms, including their social media, to carry out marketing activities to build their businesses. Apart from that, through this activity, they can add practical skills to the ability to create content that has been done